Coreografiando Mi Vida, Una Vida de Pasos (2023)
Choreographing my life: A life of Steps, is the research carried out as part of the culmination of the training process of Miguel Andrés Rodríguez Murillo in the Knowledge Validation project in the Bachelor of Performing Arts at the Antonio Nariño University. The research approach is qualitative, with a Life History methodology, whose general objective is to understand the configuration of the dancer-teacher duo based on the experiences lived by the author, as an interdisciplinary contribution to the field of dance teaching.